ผลกระทบของเขื่อนต่อการประมงในลุ่มแม่น􀃎้ำโขง - Geheb, Kim; Pukinskis, Ilse (CGIAR Challenge Program on Water and Food, 2012)
Reviews Mekong fishery basics and current literature on the impact of dams on fish migrations and habitats, biodiversity, aquaculture production and reservoir fisheries.